Vyadhi-kshamatava: An Immunotherapeutic Concept in Ayurveda - Singh, Rashmi; Sharma, Alok (Current Traditional Medicine, 2025)
Ayurveda mainly focus on treating diseases which aims at disease prevention. According to ayurveda, disease is caused by constitution, moral conduct, karma, and inappropriate contact and sensory perceptions such as sound, touch, vision, taste, and smell. These factors influence how diseases present themselves, whether they are mild, severe, acute, chronic, easily treatable, or incurable. The concept of “Vyadhikshamatva” in Ayurveda represents the fundamental principles of immunity. Ayurveda uses the terms “Vyadhi” and “Kshamatva”to describe illness and adaptation, respectively. According to Ayurveda, an imbalance in the Doshas leads to the development of diseases. In Ayurveda, immunity is referred to as “Vyadhikshamatva” and according to ayurvedic biology, Vyadhikshamatva can be correlated to the concept of immunity. Sahaj bala, Kalaj and Yuktikrit bala refer to innate immunity and acquired immunity. The current work is focus on the concept of immunity in ayurveda. Various literatures were explored from different sources such as ancient textbooks and refer. References to highlight ayurvedic immunity concept and management of disease by executing different ayurvedic principles. The result highlight the concept of Vyadhikshamatva as mentioned in Ayurvedic text which considered immunity. Therefore, the present work could contribute in the area of ayurvedic biology and explore the concept of Vyadhikshamatva with the immunity in future.
Keywords: doshas